Evaluating the barrier of typical production factor flow in the Chengdu-Chongqing Urban Agglomeration based on multi-source big data - Zhang, Yang; Wang, Xingping; Ji, Mengrong; Chen, Yulu; Yan, Feng (Frontiers in Environmental Science, 2022)
Promoting the free flow of production factors and improving the efficiency of resource allocation is a necessary requirement for China to achieve high-quality development. Therefore, it is significant to evaluate the barrier of production factor flow and analyze its influencing factors. This study, based on the flow space theory, takes the Chengdu-Chongqing urban agglomeration as an example, constructs the factor flow barrier index (FFBI) by multi-source big data (Baidu Migration data, investment data of listed companies and patent transfer data) and improved gravity model to evaluate the barriers of three typical product factors flow (labor flow, technology flow and capital flow). Moreover, quadratic assignment procedure regression model is used to analyze how system, economic, society, culture, policy and facility factors affect the barrier of the three typical production factors flow. The results demonstrate that: 1) Regardless of the calculated intensity of production factors flow by multi-source big data or the estimated intensity of production factors flow by improved gravity model, the intensity of three typical production factors flow of Chengdu-Chongqing are the highest, and intensity of three typical production factors flow between the two cities and other cities are higher than that between other 14 cities. 2) The FFBI of Chongqing and other cities is mostly positive, and the intensity of three typical production factors flow are hindered to some extent. Labor flow is less hindered than capital and technology flow. 3) Administrative division relationships and administrative level differences have important impact on the barrier of three typical production factors flow. City pairs belonging to different provincial administrative regions or within the same administrative level have larger FFBI of three typical production factors flow. In addition, the barrier of labor and capital are positively affected by the transportation cost and the similarity of the industrial structure, respectively. These findings are of great significance for revealing the formation mechanism of the barrier of production factors flow and provide some guidance for promoting the free flow of production factors and forming a new pattern of high-quality development in Chengdu-Chongqing Urban Agglomeration.